SURFACE COMPLEXATION AND DISSOLUTION OF HEMATITE BY C1-C6 DICARBOXYLIC ACIDS AT PH = 5.0 - Duckworth O.W.; Martin S.T. (My University, 2001)
Adsorption of organic ligands to the surfaces of minerals is a ubiquitous environmental process that often regulates interfacial aqueous chemistry. In the current work, the infrared spectra of dicarboxylate ligands adsorbed to hematite are collected by attenuated total reflectance (ATR) spectroscopy. For each ligand, spectra are recorded at several concentrations at pH = 5.0. Each series of spectra is analyzed by singular value decomposition constrained to a Langmuir adsorption surface model. Oxalate, malonate, and glutarate form bidentate surface complexation structures, whereas succinate and adipate form monodentate structures. The absence of a linear trend in the qualitative form of the binding structure (e.g., bidentate for n = 0, 1, and 3 and monodentate for n = 2 and 4 where n is the length of the carbon chain between carboxylate groups) is attributed to the variation of strain energies for the geometries of possible surface complexation structures. For the bidentate ligands, a linear relationship between the Langmuir binding constant and the second acidity constant is demonstrated. The ligand-promoted dissolution rates at pH = 5.0 are also determined through batch reactor experiments. For the bidentate surface complexes, the dissolution rate at monolayer ligand surface coverage slows in the order oxalate, glutarate, to malonate. Linear relationships are found between the ligand-promoted dissolution rate constants and both the Langmuir binding constants and the second acidity constants. In contrast, succinate and adipate form monodentate surface structures that dissolve slowly, if at all. In this manner, a connection is established between the macroscopic dissolution rate and the microscopic surface complexation structures.